Carboplatin-Induced Bilateral Papilledema: A Case Report - Fischer, N. (S. Karger AG, 2009)
We report on a patient with carboplatin-induced bilateral papilledema, as it was described in the 1970s for cisplatin. Loss of visual accuracy up to full blindness, often loss of color vision and scotomas can be seen as a result of cortical blindness, macula degeneration, retrobulbar neuritis and papilledema. These symptoms are mostly unilateral and initially mild, so that more chemotherapy is given before the diagnosis is made. The symptoms are usually reversible within weeks to months after cessation of the platinum treatment. The therapeutic strategy is stopping the platinum treatment. In addition the empiric use of corticosteroids is suggested.